2007
DOI: 10.1177/1352458506073780
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and brief moderate exercise. A randomised study

Abstract: This is a randomised control study, to determine the effect of aerobic and strength exercise on physical fitness and quality of life in patients with mild multiple sclerosis (MS). Sixteen outpatients with definitive MS, aged 18-50, with an Expanded Disability Status Scale (EDSS) <4, completed the study. Every patient was evaluated according to physical fitness with peak oxygen consumption (V'O2peak), workload and anaerobic threshold; quality of life (SF-36); and degree of disability (EDSS). The patients were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 18 publications
(22 reference statements)
6
73
2
1
Order By: Relevance
“…Nevertheless, other exercise programs can also led to improve in quality of life. Previous studies of MS individuals showed beneficial effects on health-related quality of life after, 4 weeks of bicycle exercise training (Mostert, 2002), or 5 weeks of aerobic and strength exercise (Bjarnadottir, 2007). In this connection, Rampello et al (2007), found after the 8-weeks bicycle exercise training program, the subjects showed a significant increase in 3 MSQOL-54 scale scores (emotional well-being, energy, and health distress).…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, other exercise programs can also led to improve in quality of life. Previous studies of MS individuals showed beneficial effects on health-related quality of life after, 4 weeks of bicycle exercise training (Mostert, 2002), or 5 weeks of aerobic and strength exercise (Bjarnadottir, 2007). In this connection, Rampello et al (2007), found after the 8-weeks bicycle exercise training program, the subjects showed a significant increase in 3 MSQOL-54 scale scores (emotional well-being, energy, and health distress).…”
Section: Discussionmentioning
confidence: 75%
“…21 Additionally, there was a trend towards improvement in fitness in the group that took part in a programme for 5 weeks (measured as Graded Exercise Test). 23 There was no change in fitness in the studies with a 3 week intervention with a 23 week home exercise programme (HEP). [20][21][22]24 Effect on activity…”
Section: Effect On Body Structure and Functionmentioning
confidence: 95%
“…Aerobic and combined aerobic and resistance training interventions have improved cardiorespiratory fitness along with beneficial changes in walking performance [46,47], spatiotemporal gait parameters [48], and symptomatic fatigue [46,47,[49][50][51] in persons with MS. For example, 8 weeks (3x/week) of moderate intensity leg cycling resulted in a significant increase in VO 2peak measured on a leg cycle ergometer, 6MW distance, and self-reported energy levels in 11 persons with MS who had moderate disability (mean EDSS=3.5) [46]. Exercise training interventions that primarily involved resistance training have improved muscular fitness, as well as walking performance [52][53][54][55][56], and symptomatic fatigue [49,51,55,57] in persons with MS. For example, significant improvements in knee flexor peak torque measured on a seated dynamometer, and T25FW and 500 MW performance were observed following 26 weeks of resistance (4x/ week) and aerobic training (1x/week) in 91 persons with MS who had a range of disability (EDSS range=1-5.5) [16].…”
Section: Exercise Training and Its Influence On Physical Fitness In Msmentioning
confidence: 99%